When the personal becomes political: The impact of the Dobbs decision on women with cancer. Issue 2 (7th November 2022) - Meisel, Jane Lowe; Harrington, Amy; Whaley, Natalie; Vitek, Wendy; O'Regan, Ruth M.
Abstract : Approximately 6400 pregnant women are diagnosed with cancer in the United States each year, and the recent decision by the Supreme Court to overturn the constitutional right to abortion will prevent many of these women from making critical decisions about their medical treatment. In many cases, lack of access to safe first‐trimester abortions may compromise these patients' cancer outcomes significantly, reducing their chances of living long enough to raise their child in the first place.